IDENTIFICATION OF PROBLEM SITUATIONS IN FUNCTIONAL DIAGNOSTICS OF INTELLIGENT BUSINESS SYSTEMS - Vasyl Lavrentiyovych Lysytskyi; Mariia Olegivna Boiko (Вісник Національного технічного університету "ХПÌ": Системний аналіз, управління та інформаційні технології, 2020)
The paper discusses the issues of increasing the efficiency of production activities of an intelligent business system operating in a dynamic environment by reducing its losses by creating a subject technology for reliable identification of problem situations in the process of functional diagnostics of a business system. The object of the research is an intelligent business system of the IT industry, which produces intelligent products, the results of which depend on the mental abilities of its personnel, who own effective intelligent information technologies. The problem-containing environment was chosen as the basis for analyzing the problem situation, in the depths of which the problem situation arises, develops and manifests itself. A problem-containing environment is characterized by structure and behavior. The behavior of the problem-containing environment is determined by the multidimensionality of the ongoing business processes, their interaction and dynamics. To identify deterministic and non-deterministic problem situations, it is proposed to set them by bipartite graphs and use the technology of inference based on precedents, which has serious advantages over the method of inference based on knowledge. In this work, a cognitive method is used to analyze problem situations of an intelligent business system. The basis of cognitive analysis is formed by the problem-containing environment, in the depths of which the problem situation arises. To study the problem-containing environment, the method of analysis of hierarchies is used, the basis of which is a hierarchy which is a system of levels, each of which consists of elements, factors of the problem-containing environment and an intelligent business system. A complex of models has been developed to construct a bipartite graph of a problem situation and to analyze its problem-containing environment. On the basis of a complex of models, a subject technology for identifying problem situations arising in the process of functional diagnostics of intelligent business systems has been created. The results obtained can be used as a theoretical platform for creating an information technology for functional diagnostics of intelligent business systems operating in a dynamic environment.